ANALYZING THE USES OF SOCIETAL MARKETING CONCEPT OF BANK: A STUDY ON A PRIVATE BANK - Rain, Navid Jun Nu; Roy, Dipu; Molla, Mijanur Rahman; Mamun, Abdullah Al; Nayeem, Md. Azizul Islam (American International Journal of Multidisciplinary Scientific Research, 2022)
In the era of globalization, every company is changing their marketing policy due to gradually increasing competitors in the existing market where social marketing is changing and maintaining the behavior of people a society. Nowadays social marketing is not a new concept in Bangladesh, especially in the banking sector. The main objective of this study is to analyze the uses of the societal marketing concept of a private Bank Limited. In this study, the quantitative and qualitative method is followed by the authors. To identify the social marketing concept qualitative and quantitative method is used in this study. A non-probability convenience sampling method has been used for the study purpose. In this study, the targeted population was executives and customers of a private Bank Limited, Jhumjhumpur Branch, Jashore. Both primary and secondary data have been used in this study where primary data was collected from the survey questionnaire and the secondary was collected from different journals, newspapers, books, websites of banks, etc. For the study purpose, 100 sample sizes were taken and the researchers have used the Five-point Likert scale technique as sample scaling where 5=Strongly Disagree, 4=Disagree, 3=Neutral, 2=Agree, 1=Strongly Agree. From the study, the authors suggested that the use of societal marketing is profitable for the marketer because it can easily grasp customers’ attention. JEL Classification Codes: M33, M40.